Efficacy of Helicobacter pylori eradication therapies in Korea: A systematic review and network meta‐analysis. Issue 4 (19th April 2017) - Jung, Yoon Suk; Park, Chan Hyuk; Park, Jung Ho; Nam, Eunwoo; Lee, Hang Lak
Abstract: Background: The efficacy of Helicobacter pylori eradication regimens may depend on the country where the studies were performed because of the difference in antibiotic resistance. We aimed to analyze the efficacy of H. pylori eradication regimens in Korea where clarithromycin resistance rate is high. Methods: We searched for all relevant randomized controlled trials published until November 2016 that investigated the efficacy of H. pylori eradication therapies in Korea. A network meta‐analysis was performed to calculate the direct and indirect estimates of efficacy among the eradication regimens. Results: Forty‐three studies were identified through a systematic review, of which 34 studies, published since 2005, were included in the meta‐analysis. Among 21 included regimens, quinolone‐containing sequential therapy for 14 days (ST‐Q‐14) showed the highest eradication rate (91.4% [95% confidence interval [CI], 86.9%‐94.4%] in the intention‐to‐treat [ITT] analysis). The eradication rate of the conventional triple therapy for 7 days, standard sequential therapy for 10 days, hybrid therapy for 10‐14 days, and concomitant therapy for 10‐14 days was 71.1% (95% CI, 68.3%‐73.7%), 76.2% (95% CI, 72.8%‐79.3%), 79.4% (95% CI, 75.5%‐82.8%), and 78.3% (95% CI, 75.3%‐80.9%), respectively, in the ITT analysis. In the network meta‐analysis, ST‐Q‐14 showed a better comparative efficacy than the conventional triple therapy, standard sequential therapy, hybrid therapy, and concomitant therapy. In addition, tolerability of ST‐Q‐14 was comparable to those regimens. Conclusion: In Korea, ST‐Q‐14 showed the highest efficacy in terms of eradication and a comparable tolerability, compared to the results reported for the conventional triple therapy, standard sequential therapy, hybrid therapy, and concomitant therapy.